Toboli Main Terminal Performance Analysis At The District Transportation Service Parigi Moutong - Subhan Haris (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2023)
The primary objective of this study is to conduct an analysis of the performance of the passenger terminal for road transport in Toboli, situated in the Parigi Moutong Regency. The research approach employed is descriptive qualitative, and the data analysis is based on Agus Dwiyanto's theoretical indicators. The study adopts a qualitative descriptive method, involving the purposive selection of 5 informants. The analytical process comprises data collection, data condensation, data presentation, and the formulation of conclusions or validation. The findings of the research highlight that the performance of the Toboli Passenger Terminal for Road Transport in Parigi Moutong Regency has been adversely affected by the COVID-19 pandemic. The terminal's productivity, as exemplified by the alignment between output and inputs, is notably low. This is evident through the actual versus targeted income and the failure to tap into potential alternative revenue sources. Regarding service quality, including empathy, satisfaction, and justice, the assessment reveals that these aspects are significantly lacking. The responsiveness of the Toboli Main Terminal is characterized by a low rating, underscored by the absence of voice and exit mechanisms. Moreover, the responsibilities of the Toboli Terminal are evaluated as deficient, illustrated by the inconsistent administration of services and management patterns. In terms of accountability, the Toboli Main Terminal is classified as having insufficient accountability due to inadequate reporting aligned with the terminal management's core duties and functions.